Systematic review on economic hardship, debt and psychological well-being in western countries - Thompson, Paul Wesley (International Journal Of Community Medicine And Public Health, 2021)
Financial hardship is a phenomenon which mediates many other factors in life regardless of age group one of many is well-being. Well-being is a multi-disciplinary term. This paper will investigate existing literature on the effect of financial hardship on well-being using systematic review to minimize the biases. The data will be systematically searched with following databases: Wiley-online library, Google scholar, JSTOR, Tandfonline and Emerald. The present study is a systematic review of English language research of 2010 to 2020 research papers on financial hardship and well-being. The databases used in the research are Wiley Online Library, Google Scholar with keywords financial hardship, financial pressure, financial challenges, stress, wellbeing, anxiety, psychological well-being. 81 studies were excluded and 12 studies were selected after reviewing the title and abstract of 93 studies based on the PRISMA. The inclusion and exclusion criteria allow studies of 2010 to 2021 to be considered. Fewer data was present in the subject of wellbeing and financial stress. However, the results show impact of both variables. Financial pressure leads to poor wellbeing and other factors such as lack of social support, unhealthy family environment and dept can robust the impact. The research makes a unique new contribution in research, lending support for policy, academic theory, new contributions to current literature not found elsewhere, especially mental health management policy.